Three-generational households: A case study on the relational resources and the church as agent of socialization amidst community-based trauma on the Cape Flats - Roberths-Beyers, Tamlynn Jane (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.